Concept Mapping Influence on Student Interest in Basic Technology in Junior Secondary School in Yenagoa Local Government Area - Charity Okardi; Tuesday Ebikebuna (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study examined Concept Mapping Influence on Student Interest in Basic Technology in Junior Secondary School in Yenagoa Local Government Area. Quasi-experimental design was used. Two research questions and two hypotheses tested at 0.05 level of significance were used to guide the study. The study population comprised 4502 JSS1I junior secondary school Basic technology students in public schools in Yenagoa Local Government Area of Bayelsa. Sample of 400 JSS11 Basic Technology students was selected by simple random sampling technique for the study. Research instruments for data collection was “Basic Technology Interest Inventory Scale”. The instrument was validated by an expert and three subject teachers. The Reliability of the instrument was established using Pearson Product Moment Correlation Coefficient of 0.73. The collected data were analysed, Mean and Standard Deviation were used to answer the Research questions while z-test was used to test the Hypotheses at 0.05 level of significance. Findings of the study revealed that Students that were exposed to concept mapping instructional strategy had a higher interest in Basic Technology than their counterparts taught using lecture method. Based on the findings it was recommended that Basic Technology teachers should be encouraged to use concept mapping strategy for effective teaching and learning to arouse students’ interest.